Effects of Game-Based Learning on Improving Grammar Skills of Grade 9 Students - Marko L. Aratea; Mark Anthony C. Pasubillo (Magister Program of English Education, Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2024)
As the educational system transcends to 21st-century learning, various methods in the teaching-learning process are used to motivate students, one of which is game-based learning. This study explores the effects of game-based learning in improving the grammar skills of grade 9 students at Regional Science High School-III, Philippines. The results from the 1st quarter item analysis elicited the least learned competency, which allowed researchers to examine and determine the effects of game-based learning in improving the English grammar proficiency of the 143 grade 9 students, particularly in the use of modals. The study used a quasi-experimental research design, where the researchers adopted an assessment tool to determine the students’ English grammar proficiency level. The teachers assigned the experimental group with 8 game-based lessons and the control group who experienced the traditional lessons. The researchers used a paired sample t-test using the Jamovi software. The study found that there is a highly significant difference between the pre-test and post-test scores of the respondents before and after the integration of game-based learning lessons, resulting in the rejection of the null hypothesis. Furthermore, for English teachers, the intervention is perceived as beneficial in improving the English grammar skills of the learners. The study presented the description of various game-based lessons and determined the respondents’ proficiency levels. It was found that students progressed from being developing proficient to proficient when game-based lessons were applied. Thus, game-based learning is effective as it also makes the learning environment fun, conducive, exciting, and learner-centered.